1958
DOI: 10.1002/recl.19580771209
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of acetylenic ethers XXXIII: The addition of ethoxyethyne to diphenylketene

Abstract: Ethoxyethyne reacts easily with diphenylketene. I. T h e nature of the product depends upon the reaction temperature and the solvent. In benzene at room temperature, a 34 yo yield of l-,phenyl-2-ethoxy-4-hydroxynaphthalene, VI, is obtained, whereas in nitromethane a t -20" the product is l.ldiphenyl-2-ethoxycyc/obut-2-ene-4-one, XXX. These structures have been proved by several reactions and by synthesis of degradation products. Similar reactions have been performed between l-ethoxy-l-propyne (Xxxnr. R = CPHS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A temperature of 120 °C was initially selected for this reaction on the basis of a review of conditions previously reported for related transformations involving alkynyl ethers. The retro-ene reaction of alkynyl ethers to form ketenes 12 was first observed in the laboratories of Ficini 13 and Arens, 14 and Ficini appears to have been the first to employ this process for the synthesis of amides. Subsequent researchers have applied this process to generate ketenes for cyclizations leading to lactones, 15 lactams, 16a and cyclic imides.…”
Section: Jocarticlementioning
confidence: 99%
“…A temperature of 120 °C was initially selected for this reaction on the basis of a review of conditions previously reported for related transformations involving alkynyl ethers. The retro-ene reaction of alkynyl ethers to form ketenes 12 was first observed in the laboratories of Ficini 13 and Arens, 14 and Ficini appears to have been the first to employ this process for the synthesis of amides. Subsequent researchers have applied this process to generate ketenes for cyclizations leading to lactones, 15 lactams, 16a and cyclic imides.…”
Section: Jocarticlementioning
confidence: 99%
“…For the synthesis of 9a – 9n , solutions of ethoxyethyne and the amine trap 6 in toluene were mixed on the flow system using a T-mixer. All reactions were conducted with a residence time of 10 min at 180 °C.[b]Isolated yield of product of >95 % purity by 1 H NMR spectroscopy.[c]A mixture of 6 , 8i , and the cyclobutenone product of [2+2] cycloaddition4d between 3a and the ketene intermediate was recovered.[d]Not carried out.…”
Section: Resultsmentioning
confidence: 99%
“… [b] Isolated yield of product of >95 % purity by 1 H NMR spectroscopy. [c] A mixture of 6 , 8i , and the cyclobutenone product of [2+2] cycloaddition 4d between 3a and the ketene intermediate was recovered. [d] Not carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Subsequent studies provided more evidence for the presence of vinylketenes as unobserved reaction intermediates from various sources, [12][13][14] and eventually these species were directly observed in several circumstances. [15][16][17] Studies of vinylketene cycloadditions have flourished since then.…”
Section: Methodsmentioning
confidence: 97%